2013
DOI: 10.1021/jp306585t
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Calculations of the Free Energy of Binary SII Hydrogen Clathrate Hydrates for Identifying Efficient Promoter Molecules

Abstract: The thermodynamics of binary sII hydrogen clathrates with secondary guest molecules is studied with Monte Carlo simulations. The small cages of the sII unit cell are occupied by one H 2 guest molecule.Different promoter molecules entrapped in the large cages are considered. Simulations are conducted at a pressure of 1000 atm in a temperature range of 233 K to 293 K. To determine the stabilizing effect of different promoter molecules on the clathrate, the Gibbs free energy of fully and partially 2 occupied sII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…In support of our assumptions, we note that De Leeuw and co-workers computed the entropy of binary sII clathrates with different promoter molecules in 5 12 6 4 cages using Monte Carlo simulations and found it to be quite insensitive to the species of the promoters in the large cages. 21 As the ratio of 5 12 cages to 5 12 6 4 cages is 2:1, guest molecules singly occupying the 5 12 cages will contribute 5.6 ± 4.0 J/K per mole of water. On the basis of occupancies listed in Table 2, the entropy of melting for XL−SS clathrates, SS clathrates, and XL clathrates is estimated to be 26.9 ± 6.1, 28.5 ± 7.1, and 21.1 ± 1.9 J/K per mole of water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of our assumptions, we note that De Leeuw and co-workers computed the entropy of binary sII clathrates with different promoter molecules in 5 12 6 4 cages using Monte Carlo simulations and found it to be quite insensitive to the species of the promoters in the large cages. 21 As the ratio of 5 12 cages to 5 12 6 4 cages is 2:1, guest molecules singly occupying the 5 12 cages will contribute 5.6 ± 4.0 J/K per mole of water. On the basis of occupancies listed in Table 2, the entropy of melting for XL−SS clathrates, SS clathrates, and XL clathrates is estimated to be 26.9 ± 6.1, 28.5 ± 7.1, and 21.1 ± 1.9 J/K per mole of water.…”
Section: Resultsmentioning
confidence: 99%
“…These qualities of clathrates make them good candidate materials for storage and transport of natural gas and hydrogen. The maximum loading of H 2 in laboratory synthesized clathrate hydrate has reached 5.3 wt %; however, such synthesis requires extreme pressures as high as 2 kbar, which poses a high demand on the materials of reactors and high consumption of energy to create and maintain such harsh conditions. One approach to avert this drawback is to use promoter molecules to assist in the formation of clathrate hydrates at lower pressures. THF is the most commonly used promoter for synthesis of H 2 clathrates. ,,, The formation of clathrate hydrates with other promoters, such as tert -butylamine, cyclobutanone, furan, and methane, has also been investigated. ,,, Recently, methane has been proposed as a promising alternative to THF, as it can compete with H 2 for the small cages, resulting in higher loads of hydrogen . The water cages in the clathrate synthesized with THF (or other promoter) and hydrogen contain both types of guests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to a certain size, steric effects do not play a role. In our previous paper on stability of hydrogen sII hydrates we already addressed the correlation of stability (free energy) and hydrogen bonds between a promoter and host water molecules. In our paper we concluded that these hydrogen bonds are an ambiguous measure of stability of sII clathrates and free calculations are needed.…”
Section: Resultsmentioning
confidence: 99%
“…Over recent years the SR method has been applied to calculate the free energy of various phases of ice and a good agreement was obtained with the results from the FL method. Moreover, we recently studied stability of binary sII hydrogen clathrate with various promoter molecules to screen the most efficient stabilizing compounds using the SR technique . In this paper hydrogen storage in hydrogen of sH type clathrate is addressed.…”
Section: Introductionmentioning
confidence: 99%